Short Communication: Development of selected PGPR consortium to control Ralstonia syzygii subsp. indonesiensis and promote the growth of tomatoYanti Y, Warnita, Reflin. 2018. Short Communication: Development of selected PGPR consortium to control Ralstoni - YULMIRA YANTI; WARNITA WARNITA; REFLIN REFLIN; HASMIANDY HAMID (Biodiversitas Journal of Biological Diversity, 2018)
Yanti Y, Warnita, Reflin. 2018. Short Communication: Development of selected PGPR consortium to control Ralstonia syzygii subsp. indonesiensis and promote the growth of tomato. Biodiversitas 19: xxxx. A microbial consortium is a group of different species of microorganisms and acts as a community. Combinations of biocontrol strains are expected to have a better result to suppress multiple plant diseases. Our previous research had selected four plant growth promoting rhizobacteria (PGPR) strains from chili (B. pseudomycoides strain NBRC 101232, B. cereus strain CCM 2010, Bacillus toyonensis strain BCT-7112, Serratia nematodiphila strain DZ0503SBS1) and three strains from tomato (Bacillus pseudomycoides strain NBRC 101232, Bacillus toyonensis strain BCT-7112, Bacillus thuringiensis strain ATCC 10792 ) which had ability to promote growth and control Ralstonia syzygii subsp. indonesiensis indigenously. The strains were used in the development of PGPR consortiums to increase their ability for biocontrol agent of Ralstonia syzigii subsp. indonesiensis and promoting the growth of tomato. Results showed that not all strains had good compatibility to grow together. Ten consortiums were developed based on their compatibilities. All consortiums exhibited the capability to reduce bacterial wilt disease development and also promote the growth of tomato. The consortium consisted of Serratia nematodiphila strain DZ0503SBS1, B. cereus strain CCM 2010, Bacillus aryabhattai strain B8W22 and Bacillus cereus strain IAM 12605 resulted in the best ability to reduce disease development and promote growth and yield of tomato.